Norfloxacin versus trimethoprim-sulfamethoxazole in the therapy of uncomplicated, community-acquired urinary tract infections. - Goldstein, E J (1985)
In a prospective, randomized trial, norfloxacin (400 mg perorally, twice a day) was compared with trimethoprim-sulfamethoxazole (160-800 mg perorally, twice a day) in 45 patients with uncomplicated urinary tract infections. Escherichia coli was the most common isolate. Infections due to Enterobacter spp., Proteus mirabilis, Pseudomonas spp., and Staphylococcus spp. were also treated. Norfloxacin was equivalent in effectiveness and safety to trimethoprim-sulfamethoxazole, with a cure rate of 91% at the 5- to 9-day posttherapy visit and 88% at the 4- to 6-week posttherapy visit. It was well tolerated and had a low incidence of side effects.